Diagnostic dilemma of ectopic breast in axillary region among the patients attending tertiary care hospital in rural India - Krishna, Mani; Dayal, Seema (Journal of College of Medical Sciences-Nepal, 2016)
Background and objectives: Breast developmental anomalies are common. Normally there are two breasts with nipple and areola. When it is more than two breasts, it is called Polymastia. It can also be known as ectopic or accessory breast. Diagnosis is must because it shows same disease conditions which are seen in normally occurring breast tissue. The aim of present study was to know the clinical characters, symptoms and microscopic pathological, physiological changes seen with patients diagnosed with axillary accessory breast tissue. Materials and Method: Present study was conducted in tertiary care hospital in cytology and Histopathological section of Pathology in the period from January 2013 to December 2015 on axillary swelling. FNAC & histopathology were diagnostic tool. Result: The minimum age of patients with accessory breast was 10 years and maximum was 35 years, maximum number of patients; 12 (54.54%) belonging to 21 to 30 years age group. Common clinical complaint was swelling axillary region (100%). Among these patients, 21 (95.45 %) were female only one (4.54%) patient was male. Bilateral swelling was found in eight (36.36 %) cases. Clinically lipoma was most common provisional diagnosis in eight (36.36%) patients. Conclusion: Ectopic breast tissue usually presents with axillary swelling. In axillary swelling along with lipoma, lymphadenopathy, neurofibroma, sabeceous cyst accessory breast as a diagnosis should be kept in mind. Every Axillary swelling must be examined because it can be accessory breast tissue. JCMS Nepal. 2016;12(2):74-7